Application of the Hot-Fit Method in Evaluation of the Use of ePuskesmas at Community Health Care I South Denpasar - Adiningsih, Luh Yulia; Pradnyani, Putu Erma; Putri, Putu Chrisdayanti Suada; Bhoko, Coelestina Astri (Procedia of Engineering and Life Science, 2024)
ePuskesmas is a multi-user web-based application that allows simultaneous access by multiple users. It facilitates electronic patient recording and data management. The implementation of ePuskesmas services at UPTD Denpasar Selatan 1 has not been conducted previously, but the application aids the Health Department in monitoring public health data. Therefore, it is crucial to evaluate the readiness of personnel in adopting ePuskesmas using the HOT-FIT method. The aim of this study is to assess the Usage Evaluation of ePuskesmas at UPTD Puskesmas I Denpasar Selatan using the HOT-FIT Method. The research adopts a Cross-Sectional Study approach, with a sample comprising all 32 ePuskesmas users at Puskesmas I Denpasar Selatan selected through purposive sampling. Data analysis includes multivariate analysis using multiple linear regression. The findings reveal significant correlations between human, organizational, and technological factors and the net benefit of ePuskesmas usage. Specifically, multivariate analysis identifies organizational factors as the most significant predictor influencing ePuskesmas net benefit (p<0.001). This underscores the pivotal role of organizational readiness in ePuskesmas utilization. Hence, enhancing organizational structure in ePuskesmas management is essential, alongside fostering communication and organizational experience in utilizing ePuskesmas for patient recording and reporting purposes